Ocenka effektivnosti metodiki formirovanija dvigatel'nych umenij nacinajušcich futbolistov - Shagin, N. I. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
In article data of long-term pilot studies of the motive abilities of the beginning football players devoted to a problem of effective formation are proved. The developed experimental technique has allowed to raise significantly indicators of physical and technical fitness of football players of 5-6 years that has positively affected mastering soccer bases and alsohas created favorable conditions for increase in sports skill at early stages of preparation